Biological Active Peptides from Marine Sources Related to Gut Hormones - Cudennec, Benoit; Ravallec, Rozenn (Current Protein and Peptide Science, 2013)
Bioactive peptides obtained from marine species and marine by-products are showing these days a great interest in nutraceutical and pharmaceutical applications due to their wide range of biological activities. This mini-review focuses on the potential of marine peptides to be used as appetite suppressive molecules in the prevention and/or in the treatment of obesity syndrome. An important and promising aspect in the fight against obesity is the study of anorexigenic gut hormones, like cholecystokinin (CCK) and glucagon-like peptide 1 (GLP-1), that are synthetized by enteroendocrine cells in the presence of nutrients in the gastrointestinal tract. Recent works which have focused on the interaction between marine peptides and CCK and GLP-1 are here reviewed.
Keywords: protein hydrolysate